PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pengguna Shampo Clear di Kota Semarang) - Dhea Shafira; Handoyo Djoko W (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is motivated by decrease of Clear Shampoo Top Brand Index in Indonesia and also there are few complaints from consumers about the product quality. The purpose of this study aims to determine the influence of product quality and brand image as x variable to loyalty as y variable trough satisfaction as z variable. The type of this research is an explanatory research, used non-probability sampling to 100 samples which were consumer of Clear Shampoo used purposive sampling and accidental sampling.The result shows that product quality has positive influential of 0,307 to satisfaction. Brand Image has positive influential of 0,214 to satisfaction. Satisfaction has positive influential of 0,790 to satisfaction. By the result of Sobel Test obtained between product quality to loyalty trough satisfaction is 3,09763421t sum y p-value is 0,00195072. Between brand image to loyalty trough satisfaction using t sum in Sobel Test is 2,27266607 and by p-value is 0,02304631.The writer suggest that the company should continue to improve the product quality and the brand image of Clear Shampoo, so that the customer will continue to become a loyal customer. Clear shampoo should continue to deliver satisfaction to its costumer